2020
DOI: 10.7150/jca.50835
|View full text |Cite
|
Sign up to set email alerts
|

Surfactin from Bacillus subtilis induces apoptosis in human oral squamous cell carcinoma through ROS-regulated mitochondrial pathway

Abstract: Recently, ambient air particulate matter (PM) has been shown to increase the risk of oral cancer. The most common malignant tumor in the oral cavity is oral squamous cell carcinoma (OSCC). Recent studies have revealed that surfactin, a cyclic lipopeptide generated by Bacillus subtilis , has anti-inflammatory and anti-cancer properties. However, the exact anti-cancer effects of surfactin on human OSCC and underlying molecular mechanisms remain largely unknown. In the present study, we fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 37 publications
3
10
0
Order By: Relevance
“…Our findings showed that CTD induced significant ROS generation; however, pretreatment with NAC significantly rescued the CTD-associated cell proliferation and apoptosis, suggesting that CTD exerts apoptotic effects through ROS generation in oral cancer cells ( Figure 7 ). Previous studies have reported that the ROS/MAPK pathways participate in inducing apoptosis in oral carcinoma and renal cell cancer, respectively [ 45 , 46 ], and our findings are consistent with this report. These results suggested that CTD induced apoptotic changes through the activation of the ROS/JNK pathway.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings showed that CTD induced significant ROS generation; however, pretreatment with NAC significantly rescued the CTD-associated cell proliferation and apoptosis, suggesting that CTD exerts apoptotic effects through ROS generation in oral cancer cells ( Figure 7 ). Previous studies have reported that the ROS/MAPK pathways participate in inducing apoptosis in oral carcinoma and renal cell cancer, respectively [ 45 , 46 ], and our findings are consistent with this report. These results suggested that CTD induced apoptotic changes through the activation of the ROS/JNK pathway.…”
Section: Discussionsupporting
confidence: 93%
“…First, mtROS can influence many signaling pathways. For example, mtROS could activate JNK, which induces caspase activation and apoptosis in OSCC [ 90 ]; mtROS could also activate the AMP-activated protein kinase (AMPK) pathway and inhibit the STAT3 pathway, which results in the suppression of the growth and proliferation of OSCC cells [ 91 ]. Second, mtROS can damage DNA, causing cell death [ 74 , 92 ].…”
Section: Mitochondrial-targeted Therapeutic Strategies For Osccmentioning
confidence: 99%
“…Undoubtedly, ctROS also has this function. For example, ctROS damaged the MMP and induced the production of mtROS, which activated JNK and led to caspase activation in OSCC [ 90 ]. In addition, ctROS could cause the mPTP to open, after which MAP occurred in OSCC [ 97 ].…”
Section: Mitochondrial-targeted Therapeutic Strategies For Osccmentioning
confidence: 99%
“…Through the investigation of the mechanism of action of different AMPs, it was found that some AMPs cause damage to mitochondria when exercising their biological functions [ 12 , 13 , 14 ]. Mitochondria is a site for energy production in cells, playing an important role in regulating cell growth and death [ 15 ].…”
Section: Introductionmentioning
confidence: 99%